2017
DOI: 10.1128/jvi.02051-16
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Elevated in HIV Elite Controllers Reduce HIV ReplicationIn Vitroand Modulate HIV Restriction Factor Expression

Abstract: A subset of HIV-infected individuals termed elite controllers (ECs) maintain CD4 ϩ T cell counts and control viral replication in the absence of antiretroviral therapy (ART). Systemic cytokine responses may differentiate ECs from subjects with uncontrolled viral replication or from those who require ART to suppress viral replication. We measured 87 cytokines in four groups of women: 73 ECs, 42 with pharmacologically suppressed viremia (ART), 42 with uncontrolled viral replication (noncontrollers [NCs]), and 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 69 publications
1
31
1
1
Order By: Relevance
“…Infection and virus culture assay. As described previously, PBMCs were depleted of CD8 + T cells via CD8 positive selection kits (Stem Cell Technologies) and infected with CXCR4 (X4)-tropic virus (NL4-3) or CCR5 (R5)-tropic virus (81-A) at a multiplicity of infection (MOI) of 10 −2 ,10 −3 , and 10 −4 for 2 hrs [11]. Following infection, cells were washed and seeded into 96-well culture dishes at 1x10 6 cell/mL in R20 with 50 IU/mL rhIL-2.…”
Section: Prospectively Studied Subjectsmentioning
confidence: 99%
“…Infection and virus culture assay. As described previously, PBMCs were depleted of CD8 + T cells via CD8 positive selection kits (Stem Cell Technologies) and infected with CXCR4 (X4)-tropic virus (NL4-3) or CCR5 (R5)-tropic virus (81-A) at a multiplicity of infection (MOI) of 10 −2 ,10 −3 , and 10 −4 for 2 hrs [11]. Following infection, cells were washed and seeded into 96-well culture dishes at 1x10 6 cell/mL in R20 with 50 IU/mL rhIL-2.…”
Section: Prospectively Studied Subjectsmentioning
confidence: 99%
“…A recent study examined the plasma levels of 87 cytokines in four groups of women: 73 elite controllers, 42 under anti‐retroviral therapy, 42 with efficient viral replication, and 48 HIV‐uninfected individuals . It was found that HIV infection is generally associated with increased levels of stromal cell‐derived factor 1 (SDF‐1)/ C‐X‐C motif chemokine ligand (CXCL)12, the ligand of the HIV‐1 coreceptor CXCR4, whereas four cytokines (CCL14, CCL21, CCL27, and XCL1) were elevated in elite controllers but not in non‐controllers or individuals on ART.…”
Section: Cellular Activation and Further Cytokinesmentioning
confidence: 91%
“…Modest increases could be confirmed by qRT‐PCR and Western blot, but no functional assays were performed to show that IFITMs are responsible for the observed antiviral effects. Although these findings suggest a protective role of some cytokines against HIV‐1 replication in vivo , further studies are required to obtain more definitive proof because the differences in plasma levels between the groups and the antiviral effects of the individual cytokines were modest …”
Section: Cellular Activation and Further Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we identified genes that had not been studied before, whose functions were enriched into the following processes: Virus infection, immunodeficiency, apoptosis, and cytokines. Previous studies had shown that these functions are closely related to viral replication [2425]. For instance, GNG2 (encoding G protein subunit gamma 2) showed a strong correlation with HIV in the KEGG pathway analysis.…”
Section: Dicussionmentioning
confidence: 99%